Symmetry and solitude: Status and lessons learned from binational Areas of Concern. Issue 4 (2nd October 2018) - Child, Matthew; Read, Jennifer; Ridal, Jeff; Twiss, Michael
Abstract : Areas of Concern are geographically distinct areas within the waters of the Great Lakes that are contaminated to the extent that they were originally identified by the International Joint Commission's Water Quality Board and later codified in the 1987 Great Lakes Water Quality Agreement as areas requiring remedial actions. Five of the 43 Areas of Concern are binational (Canada, USA), and are located on every river or connecting channel that drains a Great Lake. Implementing an ecosystem approach, as called for in the Agreement, presents unique challenges for binational Areas of Concern due to multiple jurisdictions and communities, and hence greater institutional, program and participatory complexity. Our review of progress in each of the binational Areas of Concern suggests that a binational and ecosystem-oriented approach is underway in the St. Marys, St. Clair and Detroit River Areas of Concern, while the Niagara River and St. Lawrence River Areas of Concern are proceeding on decidedly more independent domestic tracks. Our case study analysis of the Detroit River and St. Lawrence River Areas of Concern suggest that well developed and formal governance frameworks, the establishment of informal networks, and maintaining flexibility within a science-focused approach create conditions better suited to a binational, ecosystem-oriented means of remediation.